Problemática del espacio público en la localidad Norte Centro histórico en la ciudad de Barranquilla (2013)
Downtown was the city area where Barranquilla has its origin. This area has a special meaning for being the city commerce axis. An administrative point of view change is needed to achieve an sustainable urban development. Nowadays, a great number of problems have stopped the development of the downtown since a few decades ago. Illegal occupation of public space is a growing problem, as well as is an esthetic issue, citizens' rights crash unavoidably. Attempts to solve this situation have been in vain, meanwhile all this gets more severe. This investigation tries to reach the roots of the Barranquilla downtown complex condition offering an objective proposal based on an efficient and effective answer.